Sources of Contamination with Salmonella during Processing of Frozen Shrimps - T.S., Gopalakrishna Iyer; Varma, P.R.G. (Fishery Technology, 2013)
This paper deals with the sources of contamination with Salmonella during processing of shrimps. Water from culture ponds, coastal sea Water, sea beach sand, process water, ice, shrimp-contact surfaces, door and rodent and lizard droppings were traced out to be the major sources of contamination.